Language play on Russian-language Internet forums - Marina V. Radchenko (Russian Language Studies)
The relevance of the topic is determined by the need for a more comprehensive analysis of the linguistic and creative activity of users in computer-mediated communication, achieved through language play. In informal computer-mediated communication, the phenomenon of language play, as a manifestation of linguistic creativity, serves as a means of self-presentation and entertainment, impacting all levels of the language system, primarily the orthographic and lexical level, as well as the level of word-formation. The aim of the study is thus to identify the most frequent patterns of language play in informal computer-mediated communication based on data collected from Russian-language Internet forums. Research material were texts of messages exchanged by users within the framework of informal, relaxed communication on Russian-language Internet forums, participants of which are residents of the Russian Federation, as well as post-Soviet countries and other countries around the world. Based on the material selected by means of a complete sampling from October 2022 to March 2024, the author’s card index was compiled, numbering 396 contexts in which various types of language games are presented. For the purposes of the study, methods of continuous sampling, direct observation of language use, contextual, semantic and stylistic analysis, analysis of word-formation processes as well as descriptive and analytical approach were applied. The novelty of the work is due to the specifics of the linguistic material and is associated with the analysis of specific ways of manifestation of linguistic creativity in Internet discourse. The theoretical framework of the present paper focuses on the studies of Russian and foreign scholars in the field of language play and linguistic creativity. It has been established that anonymity of communication on the forum promotes spontaneity and freedom of expression, and also creates favorable conditions for the linguistic and creative activities of communicants, realized through a language play, which is carried out using linguistic means of different levels. The analysis of the collected data made it possible to identify the most frequent language play techniques in informal computer-mediated communication on Russian-language Internet forums, such as the nonstandard use of graphic characters, the creation of nonce words and the various changes involving phraseological units, quotes and other fixed expressions. Prospects for the research are seen in further study of the linguistic and creative potential of computer-mediated communication using the material of the Russian language, as well as conducting comparative studies using primarily data from other Slavic languages.